PENYULUHAN PEMBENTUKAN ORGANISASI BISNIS NELAYAN KELURAHAN GURUAPING KECAMATAN OBA UTARA - Fadhliah M Alhadar,; Johan Fahri,; Musdar Muhammad, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
This devotion aims to answer business management with the establishment of business organizations and the management of guraping fishermen's income, whose eyes are fishermen. Methods of devotion; The focus of the discussion group (FGD) and training and monitoring methods. To the community of Fishermen's Income Management and Establishment of Fishermen's Business Organization. The result of devotion; The service was held on Saturday, August 28, 2021, located in guraping village of North Oba Subdistrict. fishing communities the importance of managing fishermen's development and the organization of fishermen's business (cooperatives).